4 M's to make sense of evidence – Avoiding the propagation of mistakes, misinterpretation, misrepresentation and misinformation. (June 2022) - Draper-Rodi, Jerry; Vaucher, Paul; Hohenschurz-Schmidt, David; Morin, Chantal; Thomson, Oliver P.
Abstract: Osteopaths are expected to keep up to date with research evidence relevant to their clinical practice and to integrate this knowledge with their own experience and their patients' values and preferences. One of the potential challenges when engaging with research is to make sense of it, to decide if it is trustworthy, and if it is applicable to the complex and context-sensitive nature of clinical practice and the care of individual people. Clinicians are increasingly exposed to (deliberate and undeliberate) misinformation and overstatements which propagate easily, including via social media. This masterclass aims to facilitate critical thinking and engagement in research for clinicians to make better-informed decisions with their patients. It was developed to support osteopaths facing these questions with the aim of empowering them to judge research themselves, detect common fallacies in the conduct and reporting of different research designs, and to increase researchers' accountability. Ultimately, we hope that by reading and considering the guidance and examples in this paper, clinicians will be better equipped to optimise the use of their (and their patients') time when facing potential sources of evidence. Mistakes, misinterpretation, misrepresentation and misinformation are discussed for each of these methods/methodologies: case reports, clinical trials, qualitative research, and reviews. Implications for Practice: This Masterclass helps osteopaths to make sense of research. It helps osteopaths decide how/when to apply research findings in their clinical practice. A simple framework to assess the literature is provided. Case reports, clinical trials, qualitative research, and reviews are detailed specifically.